Manifestasi Adab di Ruang Siber: Redefinisi Literasi Digital melalui Kitab Adabul 'Alim Wal Muta'allim - Husnul Amin; Muhamad Alif Asshidiq (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Throughout time, understanding Digital Literacy has often been limited to technical skills: being able to operate a computer, knowing how to find information on Google, or simply understanding how to use applications. Digital literacy is not only about technological expertise but also about ethical intelligence. Understanding literacy extends beyond knowing how to upload content; it also encompasses understanding the reasons and correct ways to share content so as not to harm others. This famous book, written by KH Hasyim Asy'ari, serves as the